2017
DOI: 10.1111/imb.12324
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, mRNA expression and biological activity of the pheromone biosynthesis activating neuropeptide (PBAN) from the European corn borer, Ostrinia nubilalis

Abstract: Pheromone biosynthesis activating neuropeptide (PBAN) is a member of the pyrokinin (FXPRLamide) insect neuropeptides. Here, we report the cloning of the gene Ostnu-PBAN from the E and Z pheromone strains of the European corn borer (ECB), Ostrinia nubilalis (Lepidoptera: Crambidae), a major pest of maize. The Ostnu-PBAN genomic sequence is > 5 kb in length and consists of six exons. The deduced amino acid sequence revealed a 200-residue precursor protein including a signal peptide, a 24-amino acid (aa) diapause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
(99 reference statements)
2
9
0
Order By: Relevance
“…Notably, the cDNA encoding all five neuropeptides (Spre-DH homologue, Spre-α-NP, Spre-β-NP, Spre-PBAN, and Spre-γ-NP) in this study were identical to the members of Lepidoptera 17,18,27 . The presence of 6 exons interrupted by five introns of DH-PBAN has been reported for other genera, including Marvi-DH-PBAN, since these gene products were the precursor of sex pheromone biosynthesis activating neuropeptide 16,18 (Fig. 1).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Notably, the cDNA encoding all five neuropeptides (Spre-DH homologue, Spre-α-NP, Spre-β-NP, Spre-PBAN, and Spre-γ-NP) in this study were identical to the members of Lepidoptera 17,18,27 . The presence of 6 exons interrupted by five introns of DH-PBAN has been reported for other genera, including Marvi-DH-PBAN, since these gene products were the precursor of sex pheromone biosynthesis activating neuropeptide 16,18 (Fig. 1).…”
Section: Discussionsupporting
confidence: 58%
“…The endoproteolytic cleavage, and glycine usually provide the amino group for amidation (Fig. 1) 3840 , as reported for other DH-PBAN or PBAN that shared conserved pentapeptide sequence FXPR/KL at the C-termini 1618 . Thus, amidation and physiological activity of DH and PBAN were essential, mainly for the members of Lepidoptera, Hymenoptera, Diptera, and Coleoptera 41 .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Molecular studies revealed that 64 sex pheromone production in female moths is regulated by the Pheromone 65 Biosynthesis Activating Neuropeptide (PBAN) (Raina & Kempe, 1990). Mating 66 seems will not affect the the mRNA expression of PBAN (Fodor et al, 2017), while 67 may inhibit the release of PBAN to the hemolymph and will result in a low 68 pheromone titre in the PG (Nagalakshimi et al, 2007). Nevertheless, the possible 69 links between MAG factors and PBAN are still unclear.…”
Section: Introduction 38mentioning
confidence: 99%